Ujian Nasional Dan Problem Sosial (Sebuah Analisis Terhadap Kebijakan Pendidikan Sebagai Proses Pengembangan Kepribadian) - ., Hairiyah (Literasi: Jurnal Ilmu Pendidikan, 2013)
National exam or Final examination as an instrument to determine the student’s achievement by the end of this year still become an interesting discussion to be discussed. This theme is great interesting because it has big implications on many components including on the students. This paper will discuss the implications of national exam to personality development of students. It will begin with the basic policy implemented UN and be continued with the implications of the implementation of related social problems of personality development students. The writer also reveals about the advantages and disadvantages of many educational components as a result of the implementation of the UN. Keyword; National Exam, Student’s personality development.